Perioperative Management in Parturient with Severe Preeclampsia, Obesity, and COVID-19 - Rafael Bagus Yudhistira; Muhammad Yurizar Yudhistira; Raden Theodorus Supraptomo (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2021)
The elevated cases of pregnant women infected with COVID-19 who needed to undergo caesarean section is a great challenge to anesthesiologists. Morbid obesity and preeclampsia in pregnancy are also another challenge to medical practice especially when the patient requires caesarean section. To describe the perioperative management of a morbidly obese preeclamptic patient with COVID-19. A pregnant woman with mild case of COVID-19, severe preeclampsia and obesity underwent an emergency caesarean section. Spinal anesthesia was performed using a Whitacre 26G spinal needle with 76 mm length, bupivacaine 0.5% 12.5 mg as spinal anesthesia agent and fentanyl 25 mcg as adjuvant. All operating teams use PPE according to COVID-19 guidelines and standard procedures. The operation went with a good outcome without any transmission to the operating team. The patient underwent treatment without postoperative complications. Spinal anesthesia is considered safe to be a usual technique for parturient with preeclampsia and morbid obesity. A proper COVID-19 surgery protocol is crucial in order to protect health workers handling COVID-19 patients.